2018
DOI: 10.1037/xge0000455
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic foundations of the speech-to-song illusion.

Abstract: In the "speech-to-song illusion", certain spoken phrases are heard as highly song-like when isolated from context and repeated. This phenomenon occurs to a greater degree for some stimuli than for others, suggesting that particular cues prompt listeners to perceive a spoken phrase as song. Here we investigated the nature of these cues across four experiments. In Experiment 1, participants were asked to rate how song-like spoken phrases were after each of eight repetitions. Initial ratings were correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 79 publications
8
37
0
Order By: Relevance
“…Second, we had participants produce these phrases many times in a cyclical fashion (Cummins and Port, 1998) and we measured spontaneous rate by aggregating across these repetitions. Recent research suggests that the repetition of speech causes listeners to perceive more song-like qualities (Deutsch et al, 2011;Tierney et al, 2013Tierney et al, , 2018Falk et al, 2014;Vanden Bosch der Nederlanden et al, 2015). We hypothesized that repeated productions may lead to SPRs more similar to those in music performance tasks.…”
Section: Methodsmentioning
confidence: 95%
“…Second, we had participants produce these phrases many times in a cyclical fashion (Cummins and Port, 1998) and we measured spontaneous rate by aggregating across these repetitions. Recent research suggests that the repetition of speech causes listeners to perceive more song-like qualities (Deutsch et al, 2011;Tierney et al, 2013Tierney et al, , 2018Falk et al, 2014;Vanden Bosch der Nederlanden et al, 2015). We hypothesized that repeated productions may lead to SPRs more similar to those in music performance tasks.…”
Section: Methodsmentioning
confidence: 95%
“…Falk, Rathcke, & Dalla Bella (2014) manipulated the stability of pitch contours within syllables and found that song percepts were more common for the more stable contours. Tierney et al (2018b) found that higher song ratings for song illusion stimuli were linked to more isochronous rhythmic structure and a greater tendency for syllable pitches to follow musical melodic statistics. Rathcke, Falk, & Dalla Bella (in press) found that recordings with greater sonority led to earlier and stronger transformations to song.…”
Section: Proposed Mechanisms Of the Speech-to-song Illusionmentioning
confidence: 92%
“…(2015a), Tierney et al (2018a), and Tierney et al (2018b). Second, several studies have demonstrated that a range of acoustic and musical stimulus characteristics modulate the strength of the illusion.…”
Section: Proposed Mechanisms Of the Speech-to-song Illusionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have used a variety of stimuli to examine various aspects of the Speech-to-Song Illusion, making this illusion a well-established perceptual phenomenon [16][17][18][19][20][21][22][23][24]. To provide a strong test of our age-related hypothesis about the Speech-to-Song Illusion, we attempted to maximize the likelihood that listeners would experience the Speech-to-Song Illusion by using the original stimulus recorded by [25], rather than the variety of stimuli that have been used previously [e.g., 1,8].…”
Section: Studymentioning
confidence: 99%